2017
DOI: 10.1016/j.pocean.2016.12.002
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal patterns and environmental controls of small pelagic fish body condition from contrasted Mediterranean areas

Abstract: International audienc

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
86
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 99 publications
(106 citation statements)
references
References 99 publications
4
86
0
Order By: Relevance
“…Therefore, it can be deduced that the environmental variables are more favourable for anchovy in GSA01. Indeed, anchovy belonging to GSA01 show better condition than those from other Mediterranean or Black Sea areas, possibly because of the influence of the Atlantic Ocean (Brosset et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…Therefore, it can be deduced that the environmental variables are more favourable for anchovy in GSA01. Indeed, anchovy belonging to GSA01 show better condition than those from other Mediterranean or Black Sea areas, possibly because of the influence of the Atlantic Ocean (Brosset et al 2017).…”
Section: Discussionmentioning
confidence: 98%
“…The populations of small pelagics are naturally subject to strong abundance fluctuations (Checkley, Asch, & Rykaczewski, ) which may be more pronounced in those species under heavy fisheries exploitation, where age class structure is usually truncated with very low individuals in age classes beyond 1‐ or 2‐year‐olds. Changes in the location and extent of spawning habitat for species of commercial interest have received a lot of research attention (inter alia, Brosset et al, ; Giannoulaki et al, ; Saraux et al, ). Results have shown that these changes depend on a complex interaction of environmental factors, both physical (temperature, salinity, currents, or other oceanographic structures) and biological (productivity, usually estimated with the proxy of satellite‐derived chlorophyll).…”
Section: Introductionmentioning
confidence: 99%
“…This hypothesis should be tested in future works with the present model, but also putting more focus on the recruitment level each year. A recent study by Brosset et al (2017) found that global environmental indices (such as NAO, Mediterranean indices) could not explain the observed changes in fish landings and the general decline in the condition of small pelagic fish populations in the Mediterranean Sea. According to this study, the observed changes might be rather due to a combination of more local environmental processes and/or combined with anthropogenic factors such as fishing or pollution.…”
Section: Seasonal and Interannual Bottom-up And Top-down Effects Betwmentioning
confidence: 94%